2020
DOI: 10.1007/s13394-020-00357-4
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics home-school partnerships in diverse contexts

Abstract: The school and the home are both influential contexts in which a child learns mathematics, and therefore schools and families should work collaboratively to achieve shared goals for children's mathematics learning. In culturally and linguistically diverse areas, schools have richness to draw on but may face additional challenges in engaging with parents from varying backgrounds. To understand these challenges, this study undertook a culturally focussed investigation of mathematics home-school partnerships with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Such variety in the quality of support and material provided by different schools and teachers may contribute to poor relationships between school and parents—relationships that the literature shows to be already tenuous (McGee & Spencer, 2015 ; Remillard & Jackson, 2006 ; Schnee & Bose, 2010 ; Wadham et al, 2020 ). There was certainly some evidence for this in the qualitative data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such variety in the quality of support and material provided by different schools and teachers may contribute to poor relationships between school and parents—relationships that the literature shows to be already tenuous (McGee & Spencer, 2015 ; Remillard & Jackson, 2006 ; Schnee & Bose, 2010 ; Wadham et al, 2020 ). There was certainly some evidence for this in the qualitative data.…”
Section: Discussionmentioning
confidence: 99%
“…A barrier to quality homework interactions appears to be curricular and pedagogical changes in mathematics education (Remillard & Jackson, 2006 ). Parents are less able to draw on their past mathematics educational experience because what counts as mathematics and what are appropriate learning strategies have changed (Crafter, 2012 ; de Abreu & Cline, 2005 ; McMullen & de Abreu, 2011 ; Patall et al, 2008 ; Wadham et al., 2020 ). It seems that reform mathematics may act to disempower parents as players in their children’s education (Remillard & Jackson, 2006 ).…”
Section: Literature Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…They note that changes in mathematics curricula and pedagogies mean parents are less able to draw on their own experience of learning when assisting their children. The pre-pandemic findings of Wadham et al ( 2020 ) similarly revealed tension between parent and teacher perspectives on mathematics teaching and learning. In the South African context, where multiple curriculum changes have occurred in the past two decades, this is a relevant point.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Similarly, Colegrove and Krause (2017) show how Latinx immigrant parents "use their funds of knowledge to support learning by drawing from a variety of pedagogical methods to teach their children mathematics at home " (p. 194). Takeuchi's (2018) study with Filipina mothers in Japan illustrates the tensions that immigrant parents often encounter in sharing their mathematical practices with their children (see de Abreu & Cline, 2005;Civil & Planas, 2010;Wadham et al, 2020, for similar findings in other settings). Takeuchi points out that the Filipina mothers did not openly teach their mathematics to their children and relates this to how some forms of mathematics are seen as having more value than others.…”
mentioning
confidence: 90%